How can we mitigate against increasing biophobia among children during the extinction of experience? - Soga, Masashi; Evans, Maldwyn J.; Yamanoi, Takahiro; Fukano, Yuya; Tsuchiya, Kazuaki; Koyanagi, Tomoyo F.; Kanai, Tadashi (Biological Conservation, 2020)
The ‘extinction of experience’ – the loss of direct interactions between people and nature – has the potential to increase negative attitudes towards nature (‘biophobia’). Increased biophobia has implications for biodiversity conservation, because it may lead to a reduced motivation to protect wild animals and their habitats. If biophobia among today's children is carried into adulthood, it may negatively affect future biodiversity conservation policy and outcomes. We conducted a large-scale questionnaire survey of schoolchildren in Japan, exploring several factors influencing their levels of biophobia (dislike, disgust, fear, and perceived danger) towards common invertebrates. Children's level of biophobia was negatively associated with their frequency of nature experiences and knowledge of invertebrates. It was positively associated with family members' biophobia and the degree of urbanisation surrounding the children's school. Our results suggest that the extinction of experience is likely to increase biophobia in children in the future. However, our findings also suggest that other factors can be used as counterbalances against its negative effects.
Keywords: Biodiversity conservation; Connection to nature; Human-nature interactions; Nature relatedness; Personalised ecology; Urban ecology; Urban greenspace